2004
DOI: 10.1080/02841850410004274
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to acute hydrocephalus after subarachnoid hemorrhage

Abstract: A positive correlation was found between acute hydrocephalus and the amount of subarachnoid and, more importantly, intraventricular blood. This is consistent with the literature and confirms the current pathophysiologic concepts that the acute hydrocephalus following SAH is an obstructive form of hydrocephalus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
16
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 13 publications
3
16
0
Order By: Relevance
“…Clinical studies have shown that amount of blood in the subarachnoid space and the presence of intraventricular hemorrhage increase the risk of acute hydrocephalus. 9, 10 Similar to these reports, ventricular volume was correlated with the severity of SAH and all animals with hydrocephalus had intraventricular blood in our study. Our results suggest that the amount of subarachnoid blood or presence of intraventricular blood may cause obstruction of CSF flow.…”
Section: Discussionsupporting
confidence: 89%
“…Clinical studies have shown that amount of blood in the subarachnoid space and the presence of intraventricular hemorrhage increase the risk of acute hydrocephalus. 9, 10 Similar to these reports, ventricular volume was correlated with the severity of SAH and all animals with hydrocephalus had intraventricular blood in our study. Our results suggest that the amount of subarachnoid blood or presence of intraventricular blood may cause obstruction of CSF flow.…”
Section: Discussionsupporting
confidence: 89%
“…The multivariate analysis identified hydrocephalus (OR 3.7), elderly patients (OR 5.8), and Fi3 NASAH (OR 2.3) as independent risk factors for an unfavorable outcome after NASAH. For aneurysmal SAH, previous data have shown that a diffuse bleeding pattern (Fi3) is associated with significantly higher hydrocephalus rates and CVS 17 27. This point is also supported for the Fi3 blood distribution in NASAH by the significantly higher rates of hydrocephalus, CVS and DCI compared with NASAH without Fi3 bleeding pattern (table 3).…”
Section: Discussionsupporting
confidence: 57%
“…For aneurysmal SAH it is known that hydrocephalus, CVS, and DCI are related to the pattern of hemorrhage (with highest rates for Fi3 and Fi4) 17 27. It seems to be clear that the pattern of hemorrhage should also be an important factor for hydrocephalus, CVS, and DCI in NASAH.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is in line with Hasan 5 report that acute HC could occur in the absence of ventricular bleeding as long as there was blood in the perimesencephalic subarachnoid spaces. According to Jartti, 25 the incidence of acute HC in a 180‐patient series was higher in subjects with blood throughout the anterior, lateral, and basal regions than in subjects with no blood distributed across these three areas ( P = .010).…”
Section: Discussionmentioning
confidence: 95%